Transformasi Digital Pengrajin Tas Tanggulangin: E-Business di Era Pasar Global - ivani, muhammad euro; anshori, isa (Journal MISSY (Management and Business Strategy), 2024)
Tanggulangin, a sub-district in Sidoarjo, East Java, is renowned for its leather and bag craftsmanship, significantly contributing to the local economy. However, craftsmen face challenges from global competition and the need for digital transformation. This study analyzes how digital transformation, particularly through e-business, can enhance the competitiveness of Tanggulangin craftsmen in the global market. By leveraging digital marketing strategies, craftsmen can expand their reach and attract a wider consumer base. Despite challenges in technology understanding and training, the successful implementation of innovative products and effective digital marketing strategies is essential for sustaining their businesses. Collaboration among the government, community, and entrepreneurs is crucial for creating a conducive environment for empowering small and medium enterprises (SMEs) in Tanggulangin.